ESSENTIONALS OF AGRICULTURAL ENTOMOLOGY - G.S. DHALIWAL; RAM SINGH; B.S. CHHILLAR (Ludhiana Kalyani)
this book provide an overview of all these aspects including the origine of insets,their classificatin,external and internal structure, and insect pest of agricultural importance and their management strategies.
entomology pest management useful insects
Keywords: entomology, pest management, useful insects